Leiomyosarcoma of the broad ligament: case report and literature review - (:unkn) unknown (I R O G CANADA, INC, 2000)
A 56-year-old woman with leiomyosarcoma of the broad ligament discovered in the outpatient clinic in Marmara University Medical School is presented. Treatment consisted of total abdominal hysterectomy and bilateral salpingo-oophorectomy. After. a one-year disease-free interval, the patient underwent a repeat laparotomy and recurrence of the previously excised malignant turner was removed. The patient received external radiotherapy to the pelvis with linear accelerator.
Keywords: leiomyosarcoma; treatment; radiotherapy